Analfabetismo en los padres de familia ¿afecta en el rendimiento académico de los estudiantes? - Salazar, Nelson F. (2022)
This research focused on determining how illiteracy of parents affects the academic performance of their children, for which it was necessary to implement a field study that highlighted the complex situation of rural students in the cantons of Otavalo and Antonio Ante in Ecuador. Likewise, it was pertinent to carry out a descriptive explanatory research as a nonexperimental method, since it identifies the existence of two variables, its results were processed from a social and problematizing perspective, motivating readers to apprehend and seek solutions from critical thinking and building methodologies for change. The mixed approach with which it was approached provided quali-quantitative data, resulting from the implementation of surveys and interviews, allowing to discover in context a phenomenon that for many was already non-existent. The conclusive results on the affectation of illiteracy and the learning of their children included collateral repercussions such as the development of inadequate behaviors in the families, provoking lacerating experiences of violence that alienate the upbringing, inciting negative attitudes in the educational institutions. In conclusion, illiteracy was a fact that should be analyzed in order to guarantee sustainability in the development processes implemented by school management in rural areas. This article constituted a socio-educational diagnosis as a basis for legislating in favor of students in vulnerable areas and a call to educational authorities to implement literacy strategies to mitigate the effects of the problem.